Education for Parents of Children with Gadget Addiction - Ina Dewi Ardiyani; Yunias Setiawati; Yi-Ting Hsieh (Universitas Airlangga, 2021)
Background: Inappropriate and excessive use of gadgets can cause addiction and interfere with physical, psychological, and emotional health, increase social isolation, and negatively affect development, especially in children. The resulting impact will be greatly influenced by the role of parents, family and the environment. Purpose: This study aims to understand what education can be provided to parents of children with gadget addiction, along with how parents can choose toys and alternative games for children to reduce this gadget addiction. Methods: The design used in this article was a narrative review that involved collecting and analyzing journals using the keywords